Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41540-018-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

A network of epigenomic and transcriptional cooperation encompassing an epigenomic master regulator in cancer

Abstract: Coordinated experiments focused on transcriptional responses and chromatin states are well-equipped to capture different epigenomic and transcriptomic levels governing the circuitry of a regulatory network. We propose a workflow for the genome-wide identification of epigenomic and transcriptional cooperation to elucidate transcriptional networks in cancer. Gene promoter annotation in combination with network analysis and sequence-resolution of enriched transcriptional motifs in epigenomic data reveals transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The systems biology analysis performed in this study revealed that upregulation of self-renewing genes in CD271 + melanoma cells occurs in response to the activation of E2F, MYC, and SREBF1 promoter-containing elements. Target genes containing these response elements in their promoters (summarized in Table 1) are known to hold critical roles in cell cycle progression and DNA replication, which together are required efficient cell duplication 3638 . Furthermore, gene set enrichment analysis demonstrated that CD271 + melanoma cells displayed significant correlation with high enrichment scores for the pathways containing E2F motifs and target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The systems biology analysis performed in this study revealed that upregulation of self-renewing genes in CD271 + melanoma cells occurs in response to the activation of E2F, MYC, and SREBF1 promoter-containing elements. Target genes containing these response elements in their promoters (summarized in Table 1) are known to hold critical roles in cell cycle progression and DNA replication, which together are required efficient cell duplication 3638 . Furthermore, gene set enrichment analysis demonstrated that CD271 + melanoma cells displayed significant correlation with high enrichment scores for the pathways containing E2F motifs and target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The hierarchy and casual relationship between the regulation of enhancer DNA methylation, active enhancer histone marks, transcription factor (TF) binding, and cis-regulated transcription has been challenging to define due to the epigenetic heterogeneity among cells (Jin et al, 2011;King et al, 2016;Zhu et al, 2016). While genome-wide epigenetic profiling provided insights into the relationship between DNA methylation, histone marks, and TFs and coactivators binding (King et al, 2016;Kundaje et al, 2015;Wilson and Filipp, 2018), these approaches, even at the single-cell level, did not allow resolving fast dynamics of individual epigenetic processes in heterogeneous tissues and cell populations. Thus, currently there is no clear understanding of the basis, regulation, and functional consequences of DNA methylation heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In actual physiological systems, the complexity of the protein-network generated by the histone code is complicated, since the regulatory elements of different marks are highly interconnected. Writers and erasers of histone modifications get recruited by reader proteins of other histone modifications, leading to a topologically organized array of co-existing modifications and associated multi-protein complexes that define distinct regulatory microenvironments at specific regions on chromatin impacting transcription and 3D-chromosome architecture [ 47 , 48 , 49 , 50 , 51 , 52 ]. These regulatory networks are central mediators of embryonic development, lineage determination during differentiation and cellular homeostasis [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Histone-code and Epigenetic Network: Implications For Mymentioning
confidence: 99%